Analisis Pembiayaan Peningkatan Akses Air Minum dan Sanitasi Sehat Dengan Pendekatan Cost Benefit Analysis (CBA) - Yushananta, Prayudhy; Bakri, Samsul (Politeknik Kesehatan Tanjung Karang, 2021)
The global commitment to Sustainable Development Goals (SDGs) establishes access to safe drinking water and healthy sanitation for all residents. This study analyzes the financing and economic benefits of drinking water and sanitation service interventions using the Cost-Benefit Analysis (CBA) approach. The study used secondary data from the Health Office, the Bandar Lampung City Manpower Office, and the publication of research results. Intervention costs include the fixed and annual operating costs of the intervention. Benefits are calculated from the savings in health recovery costs, avoiding lost time from work, school, and waiting for sick children, and the acquisition of productive time. The study results get a total investment cost of 2,113,190 and a total benefit of 44,727,436. Efforts to improve water and sanitation services are effective and efficient (0.057% of GDP) and profitable ( 22.20 return for every 1 investment). These results provide strong evidence for planners and decision-makers that improving water and sanitation services provides value for returns, both social and economical, and proves the possibility of accelerating the achievement of SDGs commitments.